Induction of chirality in the charge transfer complex photochemistry - Tadashi Mori (Journal of Photochemistry and Photobiology, 2023)
Electron donor and acceptor undergo association in solution to form a weak molecular complex, namely a charge transfer complex. The formation of the complex is apparent by its new low-energy absorption band. Upon photoexcitation of this charge transfer band, an intracomplex electron transfer is facilitated to form a contact ion radical pair. The theoretical basis for the complex formation and the subsequent photoinduced electron transfer process has been well established already half a century ago. Nevertheless, the charge transfer complex photochemistry is now in a renaissance, due to its synthetic utility of its radical ion pair. By intentionally sidestepped unproductive back electron transfer process, a desired product is effectively obtained with or without external reagent and/or catalyst. In addition, the photoexcitation of the complex does not require any additional photocatalyst and often conceivable with the visible light. Accordingly, various donor/acceptor pairs and synthetic applications have been emerged as novel photoreaction systems in the last two decades. Some have also addressed the stereoselective transformations. This mini review highlights the recent progress of the asymmetric photoreaction, in particular in synthetic applications, based on the photoexcitation of the charge transfer complex, in comparison with photoredox catalysis.